Analisis Wacana Kritis Pemberitaan 17+8 Tuntutan Rakyat dalam Media Online Kompas.com - Aninda Keisha Adelia Wibowo; Julyanto Ekantoro; Tira Fitriawardhani (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines how the sociopolitical reality of the “17+8 People’s Demands” Movement was constructed in the online media Kompas.com (September 1-6, 2025) following the #IndonesiaGelap action, using Teun A. van Dijk’s Critical Discourse Analysis (CDA). The results of the study show: (1) In the text dimension, there was a transformation from the us-versus-the-polarization strategy of civil society to the state’s taming of paternalistic discourse, culminating in a quantification strategy; (2) In the social cognition dimension, Kompas.com’s gatekeeping lies between the commodification of celebrity value and the press’s ideological commitment as a watchdog; (3) In the social context dimension, a defense-segmentation strategy was identified among the ruling elite. During the legitimacy crisis, the legislature offered cosmetic procedural compromises to calm the masses, while the executive and security apparatus passively maintained hegemony. This study concludes that although legal and bureaucratic language is reproduced as the state's ideological communication apparatus to tame social unrest, the Kompas.com newsroom has successfully emerged as an arena for discursive negotiation that upholds public accountability within Indonesia's process of cyber-democratization.